Cage Painting within the fifth discipline of learning organisations. (2nd June 2009) - Rimmington, Glyn M.; Alagic, Mara
Learning organisations face new challenges in the 21st century. Increased flow of trade in commodities, manufactured goods and information as well as mobility of people have led to increased global interdependence, interconnectedness and cultural diversity. People and teams within learning organisations have become globally distributed with the aid of improved communication technologies. As a result, more sophisticated approaches to developing a global mindset, understanding multiple perspectives and improving intercultural communication are needed for successful collaboration between teams and team members. A tool that has proved beneficial in educational learning environments – the Cage Painting Simulator (CPS) – can be used to improve: intercultural communication, perspective taking and development of a global mindset. In this article, we integrate the CPS-framework for intercultural communication competence and global mindset development into the Senge's theoretical framework for learning organisations, focusing on the context of globally distributed teams and team members.